(Narrator Between Reading Text and Visual Film (2000-2017 - Jabara, Kawthar Ali; Ayoob, Dhiya Abdulrazaq (Journal of Humanities & Social Sciences, 2019)
Written narratives (narrative text) and visual narrative (film text) share the fact that they both rely on specific narrative events, as well as narrative technique, the events in both of the texts go on with their different states, but what differentiates these two narrative techniques is the difference that they both have in their media system and their media. For the language of the narrative text is the word, while the language of the visual narrative is the picture. Therefor, the literary text is aimed at the intangible at second level.Although, the tool of expression is different in both of theme, they depend on the presence of a narrator in their structures, in its different forms, whether it is narrated by the author himself or by a narrator. We will not talk so long abut the definitions of the narrator and their classifications that  can be found in many references, and we find that what is important to point at in this paper is the relationship between the narrator and the director along sides with the author. And the kind of narrators by their distortive peculiarity between what is literary and what is cinematic.The research is of three sections the first and third of which deal with narrative and visual text, they also tackle the role of the omniscient narrator in narrating the story and his movements between the two texts, narrative and visual one. The second section studies the processing of the visual texts. In which it is unique to the narrative texts in the voice over which is not achieved in the written texts.
Keywords: fiction literature; read texts; visual texts; Arab cinema; post-2000 novels; narrator; voice over